2018
DOI: 10.1038/s41418-018-0251-z
|View full text |Cite
|
Sign up to set email alerts
|

STING directly activates autophagy to tune the innate immune response

Abstract: STING (stimulator of interferon genes) is a central molecule that binds to cyclic dinucleotides produced by the cyclic GMP-AMP synthase (cGAS) to activate innate immunity against microbial infection. Here we report that STING harbors classic LC-3 interacting regions (LIRs) and mediates autophagy through its direct interaction with LC3. We observed that poly(dA: dT), cGAMP, and HSV-1 induced STING-dependent autophagy and degradation of STING immediately after TBK1 activation. STING induces non-canonical autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
260
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(272 citation statements)
references
References 44 publications
10
260
2
Order By: Relevance
“…4d). In keeping with the previously established role of STING activation in augmenting autophagy 18,36,37 , we found that a majority of intracellular BCG-disA-OE bacilli were co-localized with LC3B in IFN-γ-activated primary BMDMs ( Fig. 4e-f), similar to our findings with urothelial cancer cells ( Fig.…”
Section: Macrophages Exposed To Sting Agonists Delivered By Intratumosupporting
confidence: 92%
See 1 more Smart Citation
“…4d). In keeping with the previously established role of STING activation in augmenting autophagy 18,36,37 , we found that a majority of intracellular BCG-disA-OE bacilli were co-localized with LC3B in IFN-γ-activated primary BMDMs ( Fig. 4e-f), similar to our findings with urothelial cancer cells ( Fig.…”
Section: Macrophages Exposed To Sting Agonists Delivered By Intratumosupporting
confidence: 92%
“…S7a-b). In light of the fact that increased cytokine signaling from STING activation elicits increased autophagy 18,36,37 we evaluated the formation of LC3B puncta in human 5637 urothelial cancer cells exposed to BCG-disA-OE and BCG-WT. The majority of BCG-disA-OE bacilli co-localized with LC3B suggesting enhanced autophagic targeting by BCG-disA-OE, while similar co-localization was not observed with BCG-WT ( Fig.…”
Section: Bcg-disa-oe Is Also a Strong Inducer Of Pro-inflammatory Cytmentioning
confidence: 99%
“…After autophagy initiation, autophagy-related protein 9 (ATG9) undertakes the genesis of the autophagosome along with light chain3 (LC3) undergoing lipidation, thereby resulting in elongation of the autophagosome (88). LC3 can also be recruited directly by ERGIC-loading STING and bypass the classical autophagy pathway (68,89).…”
Section: Sting Downstream Signaling Promotes Ifnα/β Expression and Aumentioning
confidence: 99%
“…In addition, the involvement of TBK1 during autophagy has been a matter of discussion. Some studies show that cells lacking TBK1 can still maintain autophagy-like events (LC3 conversion, puncta formation and autophagosomes formation) [16, 62] while other evidence suggests a critical role for TBK1 in phosphorylation of selective autophagy receptors and STING autophagosomal degradation [63, 64]. Importantly, our data in primary cells suggest that TBK1 is needed for STING-mediated autophagy…”
Section: Discussionmentioning
confidence: 57%